Can quantity of amniotic fluid reliably predict postnatal renal function in boys with posterior urethral valves: a decision curve analysis. (6th August 2017) - Harper, Luke; Waubant, Alice; Vignes, Julien; Amat, Sara; Dobremez, Eric; Lefevre, Yan; Ferdynus, Cyril
Abstract: Objective: Prenatal management of male fetuses with suspected posterior urethral valves depends on reliable markers for postnatal long‐term renal function. Whether ultrasound parameters, including the presence or absence of oligohydramnios, are reliable remains the subject of debate. We decided to evaluate the reliability of quantity of amniotic fluid to predict postnatal renal function using decision curve analysis (DCA), a method for evaluating the clinical utility of a diagnostic test. Methods: We analyzed retrospectively 51 male fetuses born with prenatally suspected posterior urethral valves between 2009 and 2012. We studied the relationship between quantity of amniotic fluid on prenatal ultrasound and the nadir creatinine during the first year of life as a proxy of postnatal renal function using DCA. Results: Twelve fetuses presented with prenatal oligohydramnios. Thirty‐one children had a normal nadir creatinine, of which one had prenatal oligohydramnios (3.2%). Thirteen had a nadir creatinine between 35 and 75 μmol/L, of which four had prenatal oligohydramnios (30.8%). Seven had a nadir creatinine >75 μmol/L, all of them had prenatal oligohydramnios. Conclusion: In this retrospective study, DCA confirms the relationship between prenatal quantity of amniotic fluid volume and postnatal renal function. © 2017 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Posterior urethral valves can be associated with poor postnatal renal function and chronic renal insufficiency. Ultrasound parameters are used to predict postnatal renal function in boys with posterior urethral valves. What does this study add? Decision curve analysis brings the notion of parent threshold for undertreatment and overtreatment. Decision curve analysis shows that presence of oligohydramnios is a reliable prognostic criterium for parents with low to intermediate thresholds.